The structure of China's oil industry: Past trends and future prospects - Michal Meidan (The Oxford Institute for Energy Studies, 2016)
China's oil sector has been dominated by three large state-owned oil companies in charge of developing the country's domestic reserves, building and operating pipelines, managing China's increasingly sophisticated downstream, and filling its strategic petroleum reserves (SPR). Over the years, as China's demand has outstripped production, they have also become major investors in the global upstream and established a presence in global refining and oil trading. They now rank among the top ten global oil companies. Yet despite China's growing international reach, its oil sector remains heavily dominated by the Chinese state. From a majority stake in the oil companies, through price setting and diplomatic support for outbound investments, the government maintains significant influence over commercial decisions. At the same time, the technical knowhow and market expertise of the National Oil Companies (NOCs) offer them an important role in policy-making. This relationship is poorly understood, but it is now set to evolve further, alongside government efforts to gradually liberalize the energy sector and reform its state owned giants. This paper provides a historic overview of the development of the Chinese oil industry, focusing on the relations between the government and the oil companies before assessing how the reform agenda outlined by President Xi Jinping and the liberalization of the oil industry is impacting government–industry relations, as well as China's global energy footprint.
Keywords: 330; Mineralölwirtschaft; Gaswirtschaft; Wirtschaftsstruktur; Geschichte; China